2018
DOI: 10.1111/cyt.12537
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathology of non‐invasive follicular thyroid neoplasm with papillary‐like nuclear features: A comparative study with similar patterned papillary thyroid carcinoma variants

Abstract: NIFTP and FVPTC show a similar distribution among the Bethesda categories hence precluding conclusive distinction on cytology. PTC-FP, in contrast, was found to have a statistically significant higher nuclear score and more commonly showed malignant cytology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 33 publications
1
35
0
Order By: Relevance
“…However, ultrasonogrophic, cytomorphologic, and molecular features have some overlap between EFVPTC and IFVPTC, making it difficult to distinguish between them clearly. Furthermore, it is difficult to distinguish IFVPTC from FN since significant number of IFVPTCs are classified as Bethesda category III (atypia of undetermined significance/follicular lesion of undetermined significance), or IV (follicular neoplasm/suspicious for follicular neoplasm) in fine needle aspiration (FNA) cytology . To assist with preoperative decision making, we attempted to focus on distinguishing IFVPTCs from follicular‐patterned neoplasms, including EFVPTC and FN based on immunohistochemistry expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, ultrasonogrophic, cytomorphologic, and molecular features have some overlap between EFVPTC and IFVPTC, making it difficult to distinguish between them clearly. Furthermore, it is difficult to distinguish IFVPTC from FN since significant number of IFVPTCs are classified as Bethesda category III (atypia of undetermined significance/follicular lesion of undetermined significance), or IV (follicular neoplasm/suspicious for follicular neoplasm) in fine needle aspiration (FNA) cytology . To assist with preoperative decision making, we attempted to focus on distinguishing IFVPTCs from follicular‐patterned neoplasms, including EFVPTC and FN based on immunohistochemistry expression.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of Asian continent being a major contributor to worldwide prevalence of thyroid cancer (according to GLOBOCON database; estimated 48% new cases in 2012), the prevalence of NIFTP in Asians has not been reported extensively as compared with the western world . There are limited studies from Asia and even fewer form India and those present have reported a significantly lower prevalence (0%‐5%) as compared to western data (15%‐25%) …”
Section: Introductionmentioning
confidence: 77%
“…Twenty-nine cases of NIFTP/FVPTC assessed in a previous study [15] could be retrieved. Of the 8 cases of PTC-FP included in that study, 6 cases were available for re-evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…For this, all PDTC cases diagnosed over the same period with available FNA smears were included. The cytological features of NIFTP/FVPTC and PTC-FP cases have been recently published in a study from the same institute [15]. These cases were re-evaluated from the perspective of the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation